IMPLEMENTASI SISTEM INFORMASI ABSENSI GURU MENGUNAKAN TEKNOLOGI FINGERPRINT DI SEKOLAH MENENGAH ATAS (SMA) NEGERI 2 MANOKWARI - Hasbi, Hasbi; Ismail, Ismail (Fakultas Teknik, Universitas Tadulako, 2020)
The aim of this study is to find out how to design teacher absence applications using fingerprints and how to fill in teacher absence applications. This research has been conducted at SMAN 2 Manokwari, data collection techniques have been performed through observation and interviews. The SDLC method is used for system development. Fingerprint-based teacher attendance applications are created using the PHP programming language. With the fingerprint-based teacher presence application, it can make it easier for schools to fill in teacher absences, teachers can be on time and manipulation of teacher presence can be monitored from the application